Diamond / copper multilayer composite material capable of being subjected to high-temperature silver-copper welding and preparation method

By covering the surface of the diamond/copper composite with high strength and low thermal expansion metal alloy material to form a sandwich structure diamond/copper multi-layer composite material, the problem of excessive thermal expansion coefficient of diamond/copper composite in the prior art during high-temperature silver-copper welding is solved, and the welding effect of low thermal expansion coefficient and high-strength is achieved, reducing application costs.

CN119659109AInactive Publication Date: 2025-03-21ANHUI SHANGXINJINGGONG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510186484.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The thermal expansion coefficient of existing diamond/copper composite materials is too high during high-temperature silver-copper welding, resulting in the welded parts being easily deformed or the ceramic sheet cracking, which cannot meet the needs of high-temperature silver-copper welding.

Method used

Diamond/copper multi-layer composite material with sandwich structure, the intermediate layer is diamond/copper composite material, and the upper and lower layers are tungsten copper, molybdenum copper or copper/molybdenum copper/copper materials respectively. By covering these high-strength and low-thermal expansion materials on the surface of the diamond/copper composite material, the thermal expansion coefficient at high temperature is reduced.

Benefits of technology

The diamond/copper multi-layer composite material with a low thermal expansion coefficient in the high-temperature silver-copper welding temperature range is realized, and can be welded with ceramics stably, reducing the deformation risk of welded parts and saving application costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119659109A_ABST
    Figure CN119659109A_ABST
Patent Text Reader

Abstract

The invention provides a diamond / copper multi-layer composite material capable of being subjected to high-temperature silver-copper welding, a preparation method of the diamond / copper multi-layer composite material and a heat dissipation device comprising the diamond / copper multi-layer composite material capable of being subjected to high-temperature silver-copper welding. The diamond / copper multilayer composite material capable of being subjected to high-temperature silver-copper welding is of a sandwich structure, a middle layer is made of a diamond / copper composite material, and an upper layer and a lower layer are respectively made of any one of tungsten copper, molybdenum copper and copper / molybdenum copper / copper (CPC material). The surface of the diamond / copper multilayer composite material is covered with the metal alloy material, so that the diamond / copper multilayer composite material has remarkably improved strength and lower thermal expansion coefficient at high temperature, and can be welded with ceramic at high temperature, so that a silver-copper solder can be used for replacing a gold-tin solder, and the application cost of the diamond / copper multilayer composite material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material, and more particularly to a diamond / copper multilayer composite material capable of high-temperature silver-copper welding and a preparation method thereof. Background Art

[0002] With the high integration and high power of electronic components, the market demand for high thermal conductivity electronic packaging materials has gradually become strong. Diamond / copper composite materials are one of the new generation of high thermal conductivity electronic packaging materials. Their thermal conductivity is >600W / (m·K) and thermal expansion coefficient is <8ppm / K (0-200℃), and they have obvious application advantages.

[0003] In practical applications, diamond / copper composite materials are connected to ceramics by welding, and the commonly used welding methods are medium-temperature gold-tin soldering and high-temperature silver-copper soldering. The medium-temperature gold-tin soldering temperature is 300-400℃, and the high-temperature silver-copper soldering temperature is about 800℃. In the medium-temperature region, the thermal expansion coefficient of diamond / copper composite materials is <10ppm / K, and they can be welded with ceramics. When the temperature reaches high, the thermal expansion coefficient is >15ppm / K. When welded with ceramics at this temperature, the thermal expansion coefficients of the two are very different, the stress in the welding surface is large, and the welded parts are prone to deformation or the ceramic pieces are cracked. Therefore, diamond / copper composite materials cannot meet the requirements of high-temperature silver-copper soldering when connected to ceramics or chips.

[0004] The cost difference between silver-copper solder and gold-tin solder is huge, which is basically the difference between silver and gold. Therefore, solving the silver-copper welding problem of diamond / copper composite materials can greatly save the application cost of diamond / copper composite materials and increase the possibility of their civilian use. Summary of the invention

[0005] Technical issues In view of the problems existing in the prior art, the present invention aims to provide a diamond / copper multilayer composite material capable of high-temperature silver-copper welding and a preparation method thereof, wherein the diamond / copper multilayer composite material capable of high-temperature silver-copper welding has a low thermal expansion coefficient within the high-temperature silver-copper welding temperature range.

[0006] Technical Solution According to a first aspect of the present invention, there is provided a diamond / copper multilayer composite material capable of high-temperature silver-copper welding, which has a sandwich structure, wherein the middle layer is a diamond / copper composite material, and the upper and lower layers are respectively selected from any one of tungsten copper, molybdenum copper, copper / molybdenum copper / copper (CPC material).

[0007] Preferably, the thickness of the upper layer and the lower layer is 0.1-1 mm respectively.

[0008] Preferably, the thickness of the middle layer is 0.5-5 mm.

[0009] Preferably, the thickness of the intermediate layer accounts for more than 50% of the total thickness of the high-temperature silver-copper solderable diamond / copper multilayer composite material, preferably more than 60%, and more preferably more than 80%.

[0010] Preferably, the volume ratio of diamond in the diamond / copper composite material is 30% to 70%.

[0011] Preferably, the thermal expansion coefficient of the diamond / copper multilayer composite material capable of high-temperature silver-copper soldering is 6-9 ppm / K in a temperature range of 0 to 800°C.

[0012] Preferably, the flexural strength of the diamond / copper multilayer composite material capable of high-temperature silver-copper welding is above 570 MPa.

[0013] Preferably, the thermal conductivity of the diamond / copper multilayer composite material capable of high-temperature silver-copper soldering is above 530 W / (mK).

[0014] The surface of conventional diamond-copper composite materials is exposed or copper-coated. The present invention coats the surface of the diamond / copper composite material with high-strength, low-thermal expansion materials such as tungsten-copper, molybdenum-copper, CPC, etc. to enhance its high-temperature strength and reduce its high-temperature thermal expansion coefficient, thereby achieving silver-copper welding of the diamond / copper composite material.

[0015] According to a second aspect of the present invention, there is provided a method for preparing the diamond / copper multilayer composite material capable of high temperature silver-copper welding according to the present invention, comprising the following steps: Step 1: Mechanically mix the diamond with a surface metal coating and copper powder uniformly, wherein the metal coating is selected from tungsten, chromium, zirconium, titanium and copper; Step 2: Grind and clean the surface of the metal foil to remove the surface oxide layer and stains, wherein the metal foil is any one selected from tungsten copper material, molybdenum copper material, copper / molybdenum copper / copper material; Step 3: Brush a layer of copper powder slurry on the surface of the metal foil in step 2 and vacuum dry it; Step 4: Load the metal foil treated in step 3 and the diamond / copper mixed powder obtained in step 1 into a graphite mold, wherein the mold material structure is a sandwich structure, wherein the upper and lower layers are metal foils, and the middle layer is the diamond-copper mixed powder, and the surface of the metal foil treated with the copper powder slurry faces the diamond / copper mixed powder; Step 5: pre-press the material assembled in step 4, and after compaction, place it in a pulse power-on pressure sintering system for heating and pressure sintering; Step 6: De-mold the sintered block from step 5, and cut and grind it into shape.

[0016] Preferably, in step 1, the particle size of the diamond with the surface metal coating is 30-800 μm, more preferably 100-400 μm; the particle size of the copper powder is 0.5-100 μm, more preferably 1-30 μm.

[0017] Preferably, the surface coating of the diamond with a surface metal coating is chromium.

[0018] Preferably, in the diamond / copper mixed powder in step 1, the volume ratio of diamond is 30% to 70%.

[0019] Preferably, in step 2, the surface polishing treatment method of the metal foil is belt polishing or sandpaper polishing, and the cleaning method is alcohol ultrasonic cleaning.

[0020] Preferably, the thickness of the metal foil is 0.1-1 mm.

[0021] Preferably, in the tungsten-copper material, the tungsten element content is 50 vol% to 80 vol%, and the remainder is copper.

[0022] Preferably, in the molybdenum-copper material, the content of the molybdenum element is 50 vol%~80 vol%, and the balance is copper.

[0023] Preferably, in the copper / molybdenum-copper / copper material, the thickness ratio of the three layers is 1:2-4:1, wherein the content of the molybdenum element in the middle layer of molybdenum-copper is 70 vol%, and the remainder is copper.

[0024] Preferably, in step 3, the copper powder slurry is prepared by mixing alcohol and copper powder. Further preferably, the mass fraction of the copper powder in the copper powder slurry is 20% to 80%.

[0025] Preferably, the pre-pressing pressure in step 5 is 5-15 MPa, and the sintering process is: Pressure during heating stage: RT-600℃ stage, pressurized 5~15MPa; When the temperature exceeds 600℃ and reaches 950℃, the pressure is increased by 25~35MPa; Pressure during cooling stage: From 950℃ to 800℃, pressurize 25~35MPa; Below 800℃, to RT stage, 0MPa; Heating rate: RT-600℃ stage, 40~55℃ / min; Above 600℃, to 950℃, 25~35℃ / min; 950℃ insulation stage, insulation for 10~30min; Then it is cooled in the furnace.

[0026] According to a third aspect of the present invention, there is provided a heat dissipation device comprising the diamond / copper multilayer composite material capable of high-temperature silver-copper soldering according to the present invention.

[0027] Beneficial Effects 1) The present invention significantly improves the strength of the multilayer composite material and reduces its thermal expansion coefficient at high temperature by covering the metal alloy material on the surface of the diamond / copper composite material, so that it can be welded with ceramics at high temperature, thereby being able to use silver-copper solder instead of gold-tin solder, reducing its application cost.

[0028] 2) The diamond / copper surface is covered with a metal alloy material. The metal alloy material has high strength and high melting point, so that the sintered blank has small burrs, is easy to grind, and has a higher yield.

[0029] 3) The diamond / copper multilayer composite material capable of high-temperature silver-copper welding according to the present invention is prepared using SPS, with easy operation of the equipment, simple process, high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A photograph of a sample of the diamond / copper multilayer composite material prepared in Example 1 and welded to an alumina ceramic capable of high-temperature silver-copper welding is shown.

[0031] Figure 2 A physical photograph of a sample of the diamond / copper composite material prepared in Comparative Example 1 welded with alumina ceramic is shown. DETAILED DESCRIPTION

[0032] The present invention will be described in detail below with reference to examples. It should be noted that the examples herein are only used to explain the present invention rather than to limit the scope of the present invention.

[0033] Source of raw materials: The chrome-plated diamond comes from Changsha Moben New Materials Co., Ltd., with a particle size of 300μm and a coating thickness of 50~100nm; Copper powder was purchased from Anhui Nalomite New Material Technology Co., Ltd. with a particle size of 1~5μm.

[0034] Molybdenum copper foil was purchased from Antai Tianlong Technology Co., Ltd., with a thickness of 0.2 mm and a molybdenum content of 70 vol%.

[0035] The tungsten copper foil was purchased from Antai Tianlong Technology Co., Ltd., with a thickness of 0.2 mm and a tungsten content of 70 vol%.

[0036] Copper / molybdenum copper / copper foil was purchased from Antai Tianlong Technology Co., Ltd. with a thickness of 0.2 mm. The thickness ratio of the three layers was 1:4:1, and the volume fraction of molybdenum in the middle molybdenum copper was 70 vol%.

[0037] Test Method The test method for thermal expansion coefficient is linear expansion method, and the test equipment is thermal expansion instrument produced by NETZSCH in Germany; The thermal conductivity test method is the laser flash method, and the test equipment is the laser thermal conductivity meter produced by NETZSCH in Germany, model LFA350; The bending strength test method is the three-point bending method, and the testing equipment is a universal testing machine.

[0038] Example 1 Diamond / copper multilayer composite materials capable of high temperature silver-copper welding were prepared according to the following steps: Step 1: Weigh 10.3 g of chrome-plated diamond and 26.2 g of copper powder, the diamond particle size is 300 μm, and the copper powder particle size is 1 μm, and mechanically mix the chrome-plated diamond and copper powder evenly; Step 2: Grind and clean the surface of the molybdenum copper foil, and use alcohol ultrasonic cleaning to remove the surface oxide layer and stains. The size of the molybdenum copper foil is Ø50*0.2mm; Step 3: Brush a layer of copper powder slurry on the surface of the molybdenum copper foil in step 2 and dry it in vacuum, wherein the copper powder slurry is a mixture of copper powder and ethanol, and the mass fraction of the copper powder is 80%; Step 4: Load the treated molybdenum copper foil obtained in step 3 and the diamond copper mixed powder obtained in step 1 into a graphite mold. The mold material structure is a sandwich structure, with molybdenum copper foils on the top and bottom and diamond copper mixed powder in the middle. The surface of the molybdenum copper foil treated with copper powder slurry faces the diamond / copper mixed powder. The mold cavity diameter in the graphite mold is 50 mm. Step 5: Pre-press the material assembled in step 4, and after compaction, put it into the pulse power-on pressure sintering system for heating and pressure sintering. The pre-pressing pressure is 10MPa, and the sintering process is: Pressure during the heating stage: RT-600℃ stage, pressurized to 10MPa; When the temperature exceeds 600℃ and reaches 950℃, the pressure is increased to 30MPa; Pressure during the cooling stage: 950-800℃ stage, pressurized to 30MPa; Below 800℃, to RT stage, 0MPa; Heating rate: RT-600℃ stage, 50℃ / min; Above 600℃, to 950℃, 30℃ / min; 950℃ holding stage, holding for 20min; Cooling with the furnace; Step 6: De-mold the sintered block from step 5, and cut and grind it into shape.

[0039] The thickness of the prepared diamond / copper multilayer composite material capable of high-temperature silver-copper welding is 3 mm, wherein the thickness of the molybdenum-copper layer on the upper and lower surfaces is 0.2 mm respectively. The performance test results are shown in Table 1.

[0040] Example 2 Diamond / copper multilayer composite materials capable of high temperature silver-copper welding were prepared according to the following steps: Step 1: Weigh 10.3 g of chrome-plated diamond and 26.2 g of copper powder, the diamond particle size is 300 μm, and the copper powder particle size is 1 μm, and mechanically mix the chrome-plated diamond and copper powder evenly; Step 2: Grind and clean the surface of the tungsten copper foil, and use alcohol ultrasonic cleaning to remove the surface oxide layer and stains. The size of the tungsten copper is Ø50*0.2mm; Step 3: Brush a layer of copper powder slurry on the surface of the tungsten copper foil in step 2 and dry it in vacuum, wherein the copper powder slurry is a mixture of copper powder and ethanol, and the mass fraction of the copper powder is 80%; Step 4: Place the treated tungsten copper foil obtained in step 3 and the diamond / copper mixed powder obtained in step 1 into a graphite mold. The mold material structure is a sandwich structure, with tungsten copper foils on the top and bottom and diamond copper mixed powder in the middle. The surface of the tungsten copper foil treated with copper powder slurry faces the diamond / copper mixed powder. The mold cavity diameter in the graphite mold is 50 mm. Step 5: Pre-press the material assembled in step 4, and after compaction, put it into the pulse power-on pressure sintering system for heating and pressure sintering. The pre-pressing pressure is 10MPa, and the sintering process is: Pressure during the heating stage: RT-600℃ stage, pressurized to 10MPa; When the temperature exceeds 600℃ and reaches 950℃, the pressure is increased to 30MPa; Pressure during the cooling stage: 950-800℃ stage, pressurized to 30MPa; Below 800℃, to RT stage, 0MPa; Heating rate: RT-600℃ stage, 50℃ / min; Over 600℃, 950℃ stage, 30℃ / min; 950℃ holding stage, holding for 20min; Cooling with the furnace; Step 6: De-mold the sintered block from step 5, and cut and polish it into shape.

[0041] The thickness of the prepared diamond / copper multilayer composite material capable of high-temperature silver-copper welding is 3 mm, wherein the thickness of the tungsten-copper layer on the upper and lower surfaces is 0.2 mm respectively. The performance test results are shown in Table 1.

[0042] Example 3 Diamond / copper multilayer composite materials capable of high temperature silver-copper welding were prepared according to the following steps: Step 1: Weigh 10.3 g of chrome-plated diamond and 26.2 g of copper powder, the diamond particle size is 300 μm, and the copper powder particle size is 1 μm, and mechanically mix the chrome-plated diamond and copper powder evenly; Step 2: Grind and clean the surface of CPC (copper / molybdenum copper / copper) foil material, and use alcohol ultrasonic cleaning to remove the surface oxide layer and stains. The size of CPC foil is Ø50*0.2mm; Step 3: Brush a layer of copper powder slurry on the surface of the CPC foil in step 2 and dry it in vacuum, wherein the copper powder slurry is a mixture of copper powder and ethanol, and the mass fraction of the copper powder is 70%; Step 4: Load the treated CPC foil obtained in step 3 and the diamond / copper mixed powder obtained in step 1 into a graphite mold. The mold material structure is a sandwich structure, with CPC foils on the top and bottom and diamond-copper mixed powder in the middle. The surface of the CPC foil treated with copper powder slurry faces the diamond / copper mixed powder. The mold cavity diameter of the graphite mold is 50 mm. Step 5: Pre-press the material assembled in step 4, and after compaction, put it into the pulse power-on pressure sintering system for heating and pressure sintering. The pre-pressing pressure is 10MPa, and the sintering process is: Pressure during the heating stage: RT-600℃ stage, pressurized to 10MPa; When the temperature exceeds 600℃ and reaches 950℃, the pressure is increased to 30MPa; Pressure during the cooling stage: 950-800℃ stage, pressurized to 30MPa; Below 800℃, to RT stage, 0MPa; Heating rate: RT-600℃ stage, 50℃ / min; Above 600℃, to 950℃, 30℃ / min; 950℃ holding stage, holding for 20min; Cooling with the furnace; Step 6: De-mold the sintered block from step 5, and cut and polish it into shape.

[0043] The thickness of the prepared diamond / copper multilayer composite material capable of high-temperature silver-copper welding is 3 mm, wherein the thickness of the CPC layer on the upper and lower surfaces is 0.2 mm respectively. The performance test results are shown in Table 1.

[0044] Comparative Example 1 Diamond / copper composites were prepared as follows: Step 1: Weigh 10.3 g of chrome-plated diamond and 26.2 g of copper powder, the diamond particle size is 300 μm, and the copper powder particle size is 1 μm, and mechanically mix the chrome-plated diamond and copper powder evenly; Step 2: Grind and clean the surface of the pure copper foil, and use alcohol ultrasonic cleaning to remove the surface oxide layer and stains. The size of the pure copper is Ø50*0.2mm; Step 3: Brush a layer of copper powder slurry on the treated pure copper surface in step 2 and dry it in vacuum, wherein the copper powder slurry is a mixture of copper powder and ethanol, and the mass fraction of the copper powder is 70%; Step 4: Place the copper foil obtained in step 3 and the diamond copper mixed powder obtained in step 1 into a graphite mold. The mold material structure is a sandwich structure, with pure copper foils on the top and bottom and diamond copper mixed powder in the middle. The copper foil surface treated with copper powder slurry faces the diamond / copper mixed powder. The mold cavity diameter in the graphite mold is 50 mm. Step 5: Pre-press the material assembled in step 4, and after compaction, put it into the pulse power-on pressure sintering system for heating and pressure sintering. The pre-pressing pressure is 10MPa, and the sintering process is: Pressure during the heating stage: RT-600℃ stage, pressurized to 10MPa; When the temperature exceeds 600℃ and reaches 950℃, the pressure is increased to 30MPa; Pressure during the cooling stage: 950-800℃ stage, pressurized to 30MPa; Below 800℃, to RT stage, 0MPa; Heating rate: RT-600℃ stage, 50℃ / min; Above 600℃, to 950℃, 30℃ / min; 950℃ holding stage, holding for 20min; Cooling with the furnace; Step 6: De-mold the sintered block from step 5, and cut and polish it into shape.

[0045] The thickness of the prepared diamond / copper composite material is 3 mm, wherein the thickness of the pure copper layer on the upper and lower surfaces is 0.2 mm respectively. The performance test results are shown in Table 1.

[0046] Table 1: Properties of the composite materials prepared in Examples 1 to 3 and Comparative Example 1

[0047] It can be seen from Table 1 that the diamond / copper multilayer composite material according to the present invention has a lower thermal expansion coefficient, more excellent mechanical properties, and the thermal conductivity meets the application requirements.

[0048] Test Case The diamond / copper composite material capable of high-temperature silver-copper brazing prepared in Example 1 and the diamond / copper composite material prepared in Comparative Example 1 were brazed with alumina ceramics at 800°C with silver-copper.

[0049] Figure 1 The actual photograph of the sample welded with the high-temperature silver-copper-weldable diamond / copper multilayer composite material and alumina ceramic prepared in Example 1 is shown. Since the high-temperature thermal expansion coefficient of the molybdenum-copper-coated diamond / copper multilayer composite material matches that of alumina (the high-temperature thermal expansion coefficient of alumina is about 8 ppm / K), after high-temperature silver-copper brazing, the stress at the welding interface is small and the welded part is not deformed.

[0050] Figure 2 The actual photographs of the samples welded with the diamond / copper composite material and alumina ceramic prepared in the comparative example prepared in Example 1 are shown. Due to the mismatch between the high temperature thermal expansion coefficients of the diamond / copper composite material and alumina, the stress at the welding interface is large and the brazed part has obvious bending.

Claims

1. A diamond / copper multilayer composite material capable of high temperature silver-copper welding, characterized in that: It has a sandwich structure, the middle layer is a diamond / copper composite material, and the upper layer and the lower layer are respectively selected from any one of tungsten copper, molybdenum copper, copper / molybdenum copper / copper.

2. The diamond / copper multilayer composite material capable of high temperature silver-copper welding according to claim 1, characterized in that: The thickness of the upper layer and the lower layer are 0.1-1 mm respectively; And / or, the thickness of the intermediate layer is 0.5-5 mm; And / or, the thickness of the intermediate layer accounts for more than 50% of the total thickness of the diamond / copper multilayer composite material capable of high-temperature silver-copper soldering.

3. The diamond / copper multilayer composite material capable of high temperature silver-copper welding according to claim 1 or 2, characterized in that: The thickness of the intermediate layer accounts for more than 60% of the total thickness of the diamond / copper multilayer composite material capable of high-temperature silver-copper welding; And / or, the volume ratio of diamond in the diamond / copper composite material is 30% to 70%; and / or, the thermal expansion coefficient of the diamond / copper multilayer composite material capable of high-temperature silver-copper soldering is 6-9 ppm / K in a temperature range of 0 to 800° C.; And / or, the flexural strength of the diamond / copper multilayer composite material capable of high-temperature silver-copper welding is above 570 MPa; And / or, the thermal conductivity of the diamond / copper multilayer composite material capable of high-temperature silver-copper soldering is above 530 W / (mK).

4. A method for preparing a diamond / copper multilayer composite material capable of high temperature silver-copper welding according to any one of claims 1 to 3, characterized in that: It includes the following steps: Step 1: Mechanically mix the diamond with a surface metal coating and copper powder uniformly, wherein the metal coating is selected from tungsten, chromium, zirconium, titanium and copper; Step 2: Grind and clean the surface of the metal foil to remove the surface oxide layer and stains, wherein the metal foil is any one selected from tungsten copper material, molybdenum copper material, copper / molybdenum copper / copper material; Step 3: Brush a layer of copper powder slurry on the surface of the metal foil in step 2 and vacuum dry it; Step 4: Load the metal foil treated in step 3 and the diamond / copper mixed powder obtained in step 1 into a graphite mold, wherein the mold material structure is a sandwich structure, wherein the upper and lower layers are metal foils, and the middle layer is the diamond-copper mixed powder, and the surface of the metal foil treated with the copper powder slurry faces the diamond / copper mixed powder; Step 5: pre-press the material assembled in step 4, and after compaction, place it in a pulse power-on pressure sintering system for heating and pressure sintering; Step 6: De-mold the sintered block from step 5, and cut and grind it into shape.

5. The method for preparing a diamond / copper multilayer composite material capable of high temperature silver-copper welding according to claim 4, characterized in that: In step 1, the diamond with a surface metal coating has a particle size of 30 to 800 μm; the copper powder has a particle size of 0.5 to 100 μm; And / or, the surface coating of the diamond having a surface metal coating is chromium; And / or, in the diamond / copper mixed powder in step 1, the volume ratio of diamond is 30% to 70%.

6. The method for preparing a diamond / copper multilayer composite material capable of high-temperature silver-copper welding according to claim 4 or 5, characterized in that: In step 1, the diamond with a surface metal coating has a particle size of 100-400 μm; and / or, in step 1, the copper powder has a particle size of 1 to 30 μm; And / or, the surface grinding treatment method of the metal foil in step 2 is belt grinding or sandpaper grinding, and the cleaning method is alcohol ultrasonic cleaning; And / or, in step 3, the copper powder slurry is prepared by mixing alcohol and copper powder.

7. The method for preparing a diamond / copper multilayer composite material capable of high-temperature silver-copper welding according to claim 4 or 5, characterized in that: The thickness of the metal foil is 0.1-1 mm.

8. The method for preparing a diamond / copper multilayer composite material capable of high-temperature silver-copper welding according to claim 4 or 5, characterized in that: In tungsten copper materials, the tungsten content is 50vol%~80vol%, and the balance is copper; And / or, in the molybdenum-copper material, the content of molybdenum element is 50 vol% to 80 vol%, and the balance is copper; And / or, in the copper / molybdenum-copper / copper material, the thickness ratio of the three layers is 1:2~4:1, wherein the content of molybdenum element in the middle layer of molybdenum-copper is 70 vol%, and the balance is copper.

9. The method for preparing a diamond / copper multilayer composite material capable of high-temperature silver-copper welding according to claim 4 or 5, characterized in that: In step 5, the pre-pressing pressure is 5-15 MPa, and the sintering process is: Pressure during heating stage: RT-600℃ stage, pressurized 5~15MPa; When the temperature exceeds 600℃ and reaches 950℃, the pressure is increased by 25~35MPa; Pressure during cooling stage: From 950℃ to 800℃, pressurize 25~35MPa; Below 800℃, at RT stage, the pressure is 0MPa; Heating rate: RT-600℃ stage, 40~55℃ / min; Above 600℃, to 950℃, 25~35℃ / min; 950℃ insulation stage, insulation for 10~30min; Then it is cooled in the furnace.

10. A heat dissipation device, characterized in that: The invention comprises the diamond / copper multi-layer composite material capable of high-temperature silver-copper soldering according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Heat dissipation plate material for high output device

    CN108352370A

  • Method for coating surface of diamond / copper composite material with copper

    CN112974809A

  • Copper diamond composite material clad with metal layer on surface as well as preparation method thereof and application thereof

    CN113210611A

  • High-thermal-conductivity and low-expansion-rate diamond / copper composite material for third-generation semiconductors and preparation method thereof

    CN118406920A

  • Through type ceramic shell for high-power solid-state microwave power device

    CN215988708U

Cited By

  • Electronic packaging heat dissipation substrate and processing technology and application thereof

    CN120280416A

  • An electronic packaging heat dissipation substrate and its processing technology and application

    CN120280416B

  • Electronic packaging heat dissipation substrates, their processing technology and applications, and their electronic packaging heat sinks

    TWI925781B